(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
ABSTRACTThe aim of this research is to study the mechanical properties and wear behavior of aluminum composite material (AMCs) reinforced with silicon carbide particles with varying percentages (0, 3, 6 and 9) wt. %. These composites samples were prepared by stir casting process. Tensile strength, compression strength, hardness and wear resistance of the prepared composites were analyzed. The result showed that adding SiC reinforced in Al matrix increased tensile strength, compression strength, wear resistance and hardness with increased wt. percentage of silicon carbide reinforced AMCs. Maximum tensile and compression strength and hardness showed at 9 wt. percentage SiC reinforced AMCs.